How Social Anxiety and Reduced Self-Efficacy Induce Smartphone Addiction in Materialistic People. (February 2018) - Lee, Yu-Kang; Chang, Chun-Tuan; Cheng, Zhao-Hong; Lin, You
Recent research has suggested that materialism influences consumers' usage of technological communication devices, especially smartphones. The current study contributes to this evolving research stream by examining more closely the dynamics of mechanisms that might potentially cause smartphone addiction. We propose self-efficacy and social anxiety as two underlying mechanisms and further test whether their mediating effects are consistent across people with differing levels of power distance belief (PDB). We also examine the moderating role of PDB at the cultural level (Study 1: China vs. the United States) and at the individual level (Study 2: Taiwan). The empirical data are analyzed using the parallel multiple mediator model proposed by Hayes. The results confirm that these two mediators explain the relationship between materialism and smartphone addiction. The mediating effects are stronger for people with a high level of PDB than for their counterparts with low PDB. Theoretical and practical implications are discussed.